Evaluasi Sifat Fisika Kimia dan Nilai Gizi Keju Berbahan Dasar Kacang Tunggak dengan Bakteri Lactobacillus bulgaricus dan Streptococcus thermophilus sebagai keju Nabati Rendah Lemak - Yola Barokah; Dudung Angkasa; Vitria Melani (Jurnal Gizi, 2018)
This study aimed to develop and evaluate the physicochemical properties and sensoryevaluation of cowpea-based cheese (CBC). CBC made from a blend of cowpea extract (500 ml)and skim milk (100 ml) which were added 1% (ratio 50:50 of Lactobacillus bulgaricus [LB] andStreptococcus thermophilus [ST]) as formula 1 (F1), 2% LB+ST as F2, and 3% LB+ST as F3. Allformulas were triplicate for total fat (TFC), calcium (CC) and lactic acid content (LAC) analysis inaccredited laboratory. Sensory evaluation was tested by 25 semi-trained panelists. In percentage,TFC of F1, F2 and F3 were 0.12%, 0.13% and 0.12%, respectively. CC of F2 in mg/100 gram wasthe highest (129.58) if compared to F1 (90.13) and F3 (110.94) while F3 was the highest (14929.66)for LAC (in mg/ml) if compared to F1 (9437) and F2 (11178.39). Only F2 has the highest acceptancefor all sensory parameter.  Keywords: cowpeas, calcium, fat, vegan cheese